The Business of Strategic Sabotage - Shimshon Bichler; Jonathan Nitzan (Review of Capital as Power, 2023)
In a recent article, Nicolas D. Villarreal claims that our empirical analysis of the relation between business power and industrial sabotage in the United States is unpersuasive, if not deliberately misleading. Specifically, he argues that we cherry-pick specific data definitions and smoothing windows to `achieve the desired results'; that these `results are driven by statistical aberrations'; and that his own choice of variables pretty much invalidates our conclusions. In this brief response, we offer an easy-to-follow, step-by-step reply to his complaints.
Keywords: P16; E24; D3; 330; business; capital as power; capital income; industry; sabotage; unemployment; Thorstein Veblen